Lithium ion battery and electric device

By dividing the secondary spherical particles into Area A and Area B in the positive electrode active material of the lithium-ion battery, and setting the order degree of area B is greater than the order degree of area A, the problem of low insertion efficiency of lithium ions under high-rate discharge conditions is solved, the orderly introduction and rapid diffusion of lithium ions are achieved, and the rate performance and cycling performance of the battery are improved.

CN119674180APending Publication Date: 2025-03-21JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411876479.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Under high-rate discharge conditions, the impedance effect at the interface of the positive electrode active material of the lithium-ion battery hinders the insertion of lithium ions, reduces the insertion efficiency and migration rate, affects the rate performance of the battery, and may cause cracking of the positive electrode active material and affects the cycling performance.

Method used

By dividing the secondary spherical particles into region A and region B, and setting the order degree of region B is greater than the order degree of region A, the structure of the positive electrode active material is optimized to ensure that lithium ions can be introduced and diffused in an orderly manner and avoid local accumulation.

Benefits of technology

The rate performance of lithium-ion batteries is improved, cracking of the positive electrode active material is avoided, and the circulation performance and service life of the battery is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674180A_ABST
    Figure CN119674180A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery and a power utilization device, the lithium ion battery comprises a positive plate, the positive plate comprises a positive current collector and a positive active material coated on at least one surface of the positive current collector, and the positive active material at least comprises one secondary sphere particle; the diameter of the secondary spherical particles is D, the secondary spherical particles are divided into a region A and a region B in the three-dimensional space, the region A is a spherical region with the center of the secondary spherical particles as the sphere center and the diameter is m, m is equal to 0.382 D, and the region B is the part, except the region A, of the secondary spherical particles; the order degree of the area A and the area B meets the condition that RA is smaller than RB. Secondary sphere particles are divided into a region A and a region B, RB is set to be greater than RA, the region B with high order degree is easier to form a lithium ion channel, the lithium intercalation performance is improved, lithium ions in an electrolyte preferentially contact the region B and are rapidly and orderly introduced through the lithium ion channel, and the rate capability of the battery is improved; the area A is used for improving the structural stability and guaranteeing the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrical devices, and in particular to a lithium-ion battery and an electrical device. Background Art

[0002] When lithium-ion batteries are discharged, lithium ions in the electrolyte migrate to the active material layer on the surface of the positive electrode and embed into the lattice of the positive electrode active material. + The positive electrode active material needs to be embedded in a very short time, but the impedance at the interface of the positive electrode active material will hinder the insertion and extraction of lithium ions, greatly reducing the insertion and extraction efficiency of lithium ions in the electrochemical system and the migration rate in the positive electrode active material, affecting the rate performance of the battery.

[0003] On the other hand, lithium ions diffuse through the grain boundaries at the interface of the positive electrode active material to the surface of the positive electrode active material particles and further migrate to the interior of the particles. During high-rate discharge, if lithium ions are not diffused in time, they will accumulate locally at the interface of the positive electrode active material. The aggregation of a large number of lithium ions can easily cause side reactions such as electrolyte decomposition. In addition, the local enrichment of lithium ions will also cause uneven lithium insertion in the positive electrode active material, generate local stress, and then cause the positive electrode active material to crack, ultimately affecting the battery's cycle performance. Summary of the invention

[0004] In order to solve the above problems and realize the orderly introduction and rapid diffusion of lithium ions by the positive electrode active material, the first aspect of the present application provides a lithium ion battery, including a positive electrode sheet, the positive electrode sheet including a positive electrode current collector and a positive electrode active material coated on at least one surface of the positive electrode current collector, the positive electrode active material includes at least one secondary spherical particle, the secondary spherical particle has a diameter D and is divided into region A and region B in a three-dimensional space, wherein the region A is a spherical region with the center of the secondary spherical particle as the sphere center and a diameter set to m, and m=0.382D, and the region B is the portion of the secondary spherical particle excluding region A; the order of the region A and the region B satisfies: R A <R B .

[0005] The secondary spherical particles are divided into region A near the inside and region B near the outside, where region B preferentially contacts the lithium ions in the electrolyte compared to region A, and the order degree R of region B is set B Greater than the order R of region A A, the region B with high order is easier to form lithium ion channels, which is beneficial to improving the lithium insertion performance. Lithium ions are quickly and orderly introduced from the electrolyte to the positive electrode sheet, thereby improving the battery's rate performance; further, the region A with low order will be more stable in structure, used to support and maintain the structure of region B, and accept lithium ions conducted from region B, so that lithium ions can be evenly diffused in the positive electrode active material, avoiding the local accumulation of lithium ions in region B with relatively poor structural stability, thereby causing the secondary spherical particles to crack. Reasonable design of the spatial size ratio between region A and region B can improve the structural stability and ensure the battery's cycle performance while achieving the orderly introduction and rapid diffusion of lithium ions in the positive electrode active material.

[0006] In some optional embodiments, the order of the region A and the region B further satisfies: 1.5R A <R B .

[0007] In some optional embodiments, the order of the region A and the region B further satisfies: 2R A <R B .

[0008] In some optional embodiments, the order test of the region A and the region B comprises the following steps:

[0009] S21: preparing a cross-section slice of the positive electrode sheet;

[0010] S22: placing the cross-section slice under a SEM and photographing it at a magnification of 1000 times to obtain a SEM image of the cross-section slice;

[0011] S23: Select one of the secondary spherical particles in the SEM image, draw a circumscribed circle thereof, divide the secondary spherical particle into region A and region B with the center of the circumscribed circle as the center of the secondary spherical particle, and use the diameter of the circumscribed circle as the diameter D of the secondary spherical particle;

[0012] S24: randomly select 10 complete first sub-particles in the region A, and select 30 complete second sub-particles in the region B, draw a tangent through the center of the circumscribed circle that is tangent to the first sub-particle or the second sub-particle, and the first sub-particle and the second sub-particle have a longest diameter, select the maximum angle between the tangent and the longest diameter, and record it as θ, 0°≤θ≤90°, when θ>30°, it is recorded as 0 points, when θ≤30°, it is recorded as 1 point, and the scores of all the first sub-particles and the second sub-particles are obtained in turn, and the sum of the scores of all the first sub-particles is the order degree R of the region A A The quotient of the sum of the scores of all the second sub-particles divided by 3 is the order degree R of the region B.B .

[0013] In some optional embodiments, the preparation of the cross-section comprises:

[0014] S11: Take a lithium-ion battery, let it stand at 25°C for 4 hours, discharge it at a rate of 0.2C to its discharge cut-off voltage, and let it stand for 30 minutes;

[0015] S12: disassembling the lithium-ion battery and obtaining the positive electrode sheet, drying it fully, and baking it in a vacuum oven at 60° C. for 2 hours;

[0016] S13: Cooling the positive electrode sheet, and preparing a cross-section of the positive electrode sheet using argon ion polishing technology.

[0017] In some optional embodiments, the order R of the region A is A ≤7. Experimental verification shows that the order of region A satisfies R A ≤7, the battery’s cycle performance and safety performance are better.

[0018] In some optional embodiments, the order R of the region B is B ≥4. Experimental verification shows that the order of region B satisfies R B ≥4, the battery’s cycle performance and safety performance are better.

[0019] In some optional embodiments, the positive electrode active material further comprises single crystal particles, wherein the number of secondary spherical particles in the positive electrode active material accounts for x ≥ 30%. Experimental verification shows that the larger the number of secondary spherical particles accounts for x, the higher the cycle retention rate of the battery. Under the condition of x ≥ 30%, the safety performance of the battery is better.

[0020] In some optional embodiments, the same element Z exists in the region A and the region B, and the element Z is one or more of Al, Zr, Sr, Sb, Mg, Ti, W, Nb, Y, Ca, Ba, B, and F. The above chemical elements are doped in the positive electrode active material to improve the structural stability of the positive electrode active material.

[0021] In some optional embodiments, the mass percentages of the element Z in the region A and the region B are respectively Z a and Z b , and satisfies: Z a <Z bRegion B has a high degree of order and its stability is relatively poor. The surface of region B is in contact with the electrolyte and will be corroded by the byproducts of the electrolyte. Therefore, compared with region A located inside, region B has a higher demand for interface stability. Therefore, more elements Z that can improve structural stability should be appropriately doped to achieve higher safety performance.

[0022] In some optional embodiments, the Z a and Z b Further satisfaction: Z a *4R A / (2R A +R B )<Z b *R B / (R A +R B ). To further eliminate the error caused by the deviation of the value, the weighted value of the region A with a small orientation value is strengthened to obtain a better doping ratio range of the element Z, thereby balancing the improvement of the interface stability brought by the doping of the element Z and the negative impact on the interface ion exchange kinetics.

[0023] In some optional embodiments, the metal elements with the highest content in the region A and the region B are both chemical elements Q, and the element Q is one of Ni, Co, Mn, Ti, V, Mo, and Fe. Among the above chemical elements, Ni, Co, and Mn combine with lithium ions to form binary or ternary metal oxides with a layered structure, which are used to improve the lithium insertion capacity of the positive electrode sheet, which is beneficial to the high-rate charge and discharge of the battery. The binary metal oxides formed by the combination of Mn or Fe and lithium can also form a spinel structure or an olivine structure, providing a three-dimensional or one-dimensional channel for the diffusion of lithium ions, increasing the diffusion rate of lithium ions in the positive electrode active material, improving the battery rate performance, and avoiding the local accumulation of lithium ions; Ti, V, and Mo are used to improve the electrochemical properties of the material, improve the structural stability of the positive electrode active material, enhance the diffusion rate of charged particles, and improve the conductivity.

[0024] The second aspect of the present application provides an electrical device, comprising the above-mentioned lithium-ion battery. Since the lithium-ion battery has the above-mentioned beneficial effects, during the high-power discharge process of the electrical device provided by the present application, the secondary spherical particles of the positive electrode active material of the positive electrode sheet can orderly introduce lithium ions and diffuse rapidly, thereby achieving high-rate charge and discharge of the battery, while avoiding local accumulation of lithium ions that cause cracking of the positive electrode active material, improving the cycle performance of the battery, and extending the service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 This is a schematic structural diagram of a lithium-ion battery roll core according to an optional embodiment of the present application;

[0027] Figure 2 This is a front view of a positive electrode sheet of a lithium-ion battery in an optional embodiment of the present application after unfolding;

[0028] Figure 3 is a cross-sectional schematic diagram of a positive electrode sheet of a lithium-ion battery according to an optional embodiment of the present application;

[0029] Figure 4 This is a cross-sectional SEM image of a positive electrode sheet of a lithium-ion battery according to an optional embodiment of the present application.

[0030] Figure 5 It is a schematic diagram of calculating the order of secondary spherical particles of a lithium-ion battery according to an optional embodiment of the present application.

[0031] Reference numerals: 2 - core, 21 - positive electrode sheet, 212 - positive electrode current collector, 210 - positive electrode active material, 2101 - secondary spherical particle, 2101a - first sub-particle, 2101b - second sub-particle, 23 - separator, 25 - negative electrode sheet. DETAILED DESCRIPTION

[0032] Embodiments of the present embodiment are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present embodiment, and should not be construed as limiting the present embodiment.

[0033] In the description of this embodiment, it should be understood that descriptions involving orientation, such as up, down, front, back, left, right, etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing this embodiment and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on this embodiment.

[0034] In the description of this embodiment, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0035] In the description of this embodiment, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in this embodiment based on the specific content of the technical solution.

[0036] Please refer to Figure 1-Figure 2 , Figure 1 The structure diagram of the winding core 2 of an embodiment of the present application is shown. Figure 2 The front view of the positive electrode sheet 21 after unfolding is shown. The common structure of the existing lithium-ion battery includes a shell with an opening at one end, a winding core 2 assembled in the shell from the opening, an electrolyte injected into the shell to immerse the winding core 2, and a cap covering the shell opening, wherein, Figure 1 The winding core 2 is formed by winding the stacked positive electrode sheet 21, the separator 23 and the negative electrode sheet 25, see Figure 2 A positive electrode active material 210 is provided on at least one side of the positive electrode current collector 212 for embedding lithium ions in the electrolyte during discharge and releasing lithium ions to transfer to the electrolyte during charge.

[0037] In a first aspect, the present application provides a lithium-ion battery, comprising a positive electrode sheet 21, wherein the positive electrode sheet 21 comprises a positive electrode current collector 212 and a positive electrode active material 210 coated on at least one surface of the positive electrode current collector 212, wherein the positive electrode active material 210 comprises at least one secondary spherical particle 2101, wherein the secondary spherical particle 2101 has a diameter D and is divided into a region A and a region B in a three-dimensional space, wherein the region A is a spherical region with a center of the secondary spherical particle 2101 as the sphere center and a diameter set to m, and m=0.382D, and the region B is the portion of the secondary spherical particle 2101 other than the region A; and the order of the region A and the region B satisfies: R A <R B .

[0038] Further, see Figure 3 , Figure 4 and Figure 5 The orderliness test of the region A and the region B comprises the following steps:

[0039] S21: preparing a cross-section slice of the positive electrode sheet 21;

[0040] S22: placing the cross-section slice under a SEM and photographing it at a magnification of 1000 times to obtain a SEM image of the cross-section slice;

[0041] S23: selecting one of the secondary spherical particles 2101 in the SEM image, drawing a circumscribed circle thereof, dividing the area A and the area B with the center of the circumscribed circle as the center of the secondary spherical particle 2101, and taking the diameter of the circumscribed circle as the diameter D of the secondary spherical particle 2101; and

[0042] S24: 10 complete first sub-particles 2101a are randomly selected in the region A, and 30 complete second sub-particles 2101b are randomly selected in the region B. A tangent line tangent to the first sub-particle 2101a or the second sub-particle 2101b is drawn through the center of the circumscribed circle, and the first sub-particle 2101a and the second sub-particle 2101b have the longest diameter. The maximum angle between the tangent line and the longest diameter is selected and recorded as θ, 0°≤θ≤90°. When θ>30°, it is recorded as 0 points, and when θ≤30°, it is recorded as 1 point. The scores of all the first sub-particles 2101a and the second sub-particles 2101b are obtained in sequence. The sum of the scores of all the first sub-particles 2101a is the order R of the region A. A The quotient of the sum of the scores of all the second sub-particles 2101b divided by 3 is the order degree R of the region B. B .

[0043] See also Figure 5 As an example, conventionally, two tangent lines tangent to the closed figure can be drawn through a point outside the closed figure, so two tangent lines tangent to the first sub-particle 2101a or the second sub-particle 2101b can be drawn through the center of the circumscribed circle, which are shown as θ and θ' in the figure. According to the rule of selecting the maximum angle, the larger angle is selected as θ, and the score is recorded according to the size of the selected maximum angle θ; it can be understood that when two angles are equal, any angle can be selected as θ.

[0044] It should be further explained that when the longest diameter of the first sub-particle 2101a or the second sub-particle 2101b and the corresponding tangent angle are smaller, it means that the growth direction of the first sub-particle 2101a or the second sub-particle 2101b is close to the radial direction of the circumscribed circle, and the sub-particles are not easy to cross and collide with each other, and the arrangement is relatively more regular, so the order is high, so it is easier for the sub-particles to form channels for lithium ion insertion and migration in the radial direction of the secondary spherical particles, so as to achieve the orderly introduction of lithium ions and the rapid migration of lithium ions into the particles to reduce the local accumulation in area B; on the contrary, the particles are arranged in a disorderly manner, the order is low, and it is difficult to form a radial depth. The lithium ion channel has considerable length. After the lithium ions are inserted, it is difficult for them to continue to migrate into the interior of the secondary spherical particles 2101. When the insertion sites near the surface of region B are filled, the positive electrode sheet 21 is saturated with lithium. The lithium ions cannot continue to undergo electrochemical reactions in the positive electrode sheet 21, thereby limiting the high-rate discharge of the battery. At the same time, under high-rate discharge conditions, a large number of lithium ions will gather around the positive electrode sheet 21 in a short period of time. If the region B is not timely for the diffusion and migration of lithium ions, lithium ions will accumulate locally on its surface, generating stress and destroying the structure of the positive electrode active material 210. This will cause irreversible damage to the battery capacity and make it difficult to guarantee the cycle performance of the battery.

[0045] Further, the secondary spherical particles 2101 are divided into a region A close to the inside and a region B close to the outside, wherein the region B is in direct contact with the lithium ions in the electrolyte compared to the region A, and the order degree R of the region B is set B Greater than the order R of region A A , the region B with high order is easier to form lithium ion channels, which is beneficial to improving the lithium insertion performance, and the lithium ions are quickly and orderly conducted from the electrolyte to the positive electrode sheet 21; further, the region A with low order has a relatively stable structure, which is used to support and maintain the structure of region B and accept the lithium ions conducted from region B, so that the lithium ions can be evenly diffused in the positive electrode active material 210, avoiding the local accumulation of lithium ions in region B with relatively poor structural stability, which in turn leads to the cracking of the secondary spherical particles 2101. Region A is defined as a spherical region with the center of the secondary spherical particle 2101 as the sphere center and a diameter of m, and m=0.382D. Reasonable design of the spatial size ratio between region A and region B can achieve the orderly introduction and rapid diffusion of lithium ions by the positive electrode active material 210 while taking into account the guarantee of structural stability and the cycle performance of the battery.

[0046] In the specific implementation process, the order of the region A and the region B satisfies: 1.5R A <R B , it has been verified by experiments that the secondary spherical particles 2101 that meet the above conditions have a battery capacity retention rate of more than 80% under 1.5C charging rate and 10C discharge rate cycle tests; further, the order of region A and region B meets: 2R A<R B , the battery capacity retention rate is as high as 89%.

[0047] In some optional embodiments, the order R of the region A is A ≤7, preferably, R A ≤5. Too high an order in region A will affect the structural stability of the positive electrode active material 210. Experimental verification shows that R A ≤5 The battery can still ensure good cycle performance at a 10C discharge rate.

[0048] In some optional embodiments, the order R of the region B is B ≥4, preferably, R B ≥7. For region B, the higher the order, the better. Based on the existing manufacturing technology of secondary spherical particles 2101, R B Not less than 7 can improve the lithium insertion ability of the positive electrode active material 210 and achieve good cycle performance of the battery at a 10C discharge rate.

[0049] In some optional embodiments, see Figure 3 , the preparation of the cross-section comprises:

[0050] S11: Take a lithium-ion battery, let it stand at 25°C for 4 hours, discharge it at a rate of 0.2C to its discharge cut-off voltage, and let it stand for 30 minutes;

[0051] S12: disassembling the lithium-ion battery and obtaining the positive electrode sheet 21, drying it fully, and then baking it in a vacuum oven at 60° C. for 2 hours;

[0052] S13: Cooling the positive electrode sheet, and preparing a cross-section of the positive electrode sheet 21 by using argon ion polishing technology.

[0053] It can be understood that the positive electrode active material 210 is formed on the surface of the positive electrode current collector 212 and has a certain thickness, and the positive electrode current collector 212 is usually an aluminum foil with a thickness less than that of the positive electrode active material 210. Figure 3 The cross-sectional schematic diagram of the positive electrode sheet 21 shown can reflect the particle composition of the positive electrode active material 210 from close to the electrolyte to away from the electrolyte, which is also consistent with the diffusion direction of lithium ions and is more suitable for evaluating the lithium insertion performance of the positive electrode active material 210.

[0054] In some optional embodiments, the positive electrode active material 210 further includes single crystal particles, and the number of the secondary spherical particles 2101 in the positive electrode active material 210 accounts for x≥30%.

[0055] In some optional embodiments, the same element Z exists in the region A and the region B, and the element Z is one or more of Al, Zr, Sr, Sb, Mg, Ti, W, Nb, Y, Ca, Ba, B, and F. The above chemical elements are doped into the positive electrode active material 210 to improve the structural stability of the positive electrode active material 210.

[0056] In some optional embodiments, the mass percentages of the element Z in the region A and the region B are Z and a and Z b , and satisfies: Z a <Z b The order of region B is high, and its stability is relatively poor. Region B is also in contact with the electrolyte and is likely to be corroded by the byproducts of the electrolyte. Therefore, more element Z that can improve the structural stability should be appropriately doped.

[0057] It should be noted that the main function of doping element Z is to improve the stability of the interface of the positive electrode active material 210 to achieve higher safety performance, but excessive element Z will affect the lithium ion channel on the surface of the secondary spherical particles 2101 and deteriorate the ion exchange kinetics at the interface. Region B has a high degree of order and its stability is relatively poor. The surface of region B is also in contact with the electrolyte and is easily corroded by the byproducts of the electrolyte. Therefore, compared with region A located inside, region B has a higher demand for interface stability, so more elements Z that can improve structural stability should be appropriately doped to achieve higher safety performance.

[0058] Due to R A <R B , and in 2R A <R B In the case of (R A +R B ) and (2R A +R B ) is called the overall orientation coefficient, and is R A Assigning a weight greater than 1 is more conducive to balancing the problem of low feature weakening in region A, and R A and R B The ratio of each to the overall orientation coefficient is called the regional orientation degree, which is used to further eliminate the deviation caused by the error of a single parameter. Since the orientation value of region A is smaller than that of region B, a weighted value is assigned to region A with a smaller orientation value for strengthening, and then the same characteristics are compared with region B to further limit Z a and Z b Satisfaction: Z a *4R A / (2R A +R B)<Z b *R B / (R A +R B ), a more accurate doping ratio range of element Z can be obtained, thereby better balancing the improvement of interface stability brought by the doping of element Z and the negative impact on the interface ion exchange kinetics, thereby achieving excellent cycle performance and safety performance of the battery.

[0059] In some optional embodiments, the metal elements with the highest content in the region A and the region B are both chemical elements Q, and the element Q is one of Ni, Co, Mn, Ti, V, Mo, and Fe. Ni, Co, and Mn among the above chemical elements combine with lithium ions to form binary or ternary metal oxides with a layered structure, which are used to improve the lithium insertion capacity of the positive electrode sheet. The binary metal oxides formed by the combination of Mn or Fe and lithium can also form a spinel structure or an olivine structure, providing a three-dimensional or one-dimensional channel for the diffusion of lithium ions, increasing the diffusion rate of lithium ions in the positive electrode active material 210, and avoiding the local accumulation of lithium ions; Ti, V, and Mo are used to improve the electrochemical properties of the material, improve the structural stability of the positive electrode active material, enhance the diffusion rate of charged particles, and improve the conductivity.

[0060] The second aspect of the present application provides an electrical device, comprising the above-mentioned lithium-ion battery. Since the lithium-ion battery has the above-mentioned beneficial effects, during the high-power discharge process of the electrical device provided by the present application, the secondary spherical particles of the positive electrode active material of the positive electrode sheet can orderly introduce lithium ions and diffuse rapidly, thereby avoiding the local accumulation of lithium ions and causing the positive electrode active material to crack, thereby improving the cycle performance of the battery and extending the service life.

[0061] The technical solution of the present application is described below in conjunction with Examples 1-13 and Comparative Examples 1-6.

[0062]

[0063]

[0064] The above Examples 1-13 and Comparative Examples 1-6 were subjected to 600-cycle cycle retention test, hot box test and EDS element analysis respectively:

[0065] The test method for 600-cycle cycle retention rate is:

[0066] Take a lithium ion battery prepared according to any of the above embodiments, place it in a constant temperature box at 25°C for more than 4 hours, and test it according to the following steps:

[0067] S31: The battery is charged at a constant current of 1.5C to 4.2V, and is charged at a constant voltage to a current of 0.025C, and is left standing for more than 15 minutes; the battery is discharged at a constant current of 10C to 2.5V, and the discharge capacity is recorded as the initial capacity, which is recorded as a;

[0068] S32: repeat the above step S21 for 600 times; record the discharge capacity at the 600th cycle, denoted as b;

[0069] S33: Calculate the 600-cycle retention rate as b / a×100%.

[0070] The hot box test method is:

[0071] Take a lithium ion battery prepared according to any of the above embodiments, place the battery in a constant temperature box at 25°C for more than 4 hours, and test it according to the following steps:

[0072] S41: The battery is discharged at a constant current of 0.1C discharge rate to 2.5V cutoff, and left to stand for 5 minutes;

[0073] S42: The battery is charged at a constant current of 0.2C to a cutoff of 4.2V, and at a constant voltage of 0.05C to a cutoff, and allowed to stand for 5 minutes;

[0074] S43: Place the battery in a heating box, set the heating rate to 5K / min, heat to 130°C, and keep it for 1 hour, then stop heating and cool it to below 30°C by self-heating;

[0075] S44: If the battery does not catch fire or emit smoke, it is considered to have passed; otherwise, it is considered to have failed. At least 6 batteries are tested in parallel for one embodiment or comparative example, and the pass rate is recorded.

[0076] The qualitative and / or quantitative analysis of the above-mentioned element Z and element Q are all tested by energy dispersive spectrometer (EDS).

[0077] The EDS element analysis method is:

[0078] S51: preparing a cross-section sample of the positive electrode sheet 21;

[0079] S52: Check the working environment of the EDS detector and calibrate the EDS system;

[0080] S53: loading the sample, collecting the EDS spectrum of the sample to be tested under the predetermined electron beam conditions;

[0081] S54: Use EDS analysis software to process and analyze the collected spectra to obtain the types and contents of the elements.

[0082] Examples 1-5 and Comparative Examples 1-3 are based on the order R of region A and region B.A , R B The control group with the variable, Examples 1 and 6-8 and Comparative Example 4 are the control groups with the proportion of secondary spherical particles x as the variable, Examples 1 and 9-11 are the control groups with the type of doping element Z as the variable, Examples 1 and 12 and Comparative Examples 5-6 are the control groups with the content of doping element Z in region A and region B as the variable, and Examples 1 and 13 are the control groups with the type of doping metal element Q as the variable. The specific comparison results are shown in Tables 1-5:

[0083] Table 1

[0084]

[0085]

[0086] As can be seen from Table 1, R A and R B The size relationship can significantly affect the cycle performance and safety of the battery. A <R B When the cycle retention rate is relatively higher, at the same time, R B The larger the value, the better the cycle retention rate. A ≤R B When the battery is used for a long time, the cycle retention rate of the battery is poor and the safety of use is poor, and the pass rate of the hot box test is almost 0.

[0087] Table 2

[0088]

[0089] It can be seen from Table 2 that the proportion x of the number of secondary spherical particles has a great influence on the cycle retention rate of the battery. The larger the proportion x of the number of secondary spherical particles is, the higher the cycle retention rate of the battery is. In the actual production process, the proportion x of the number of secondary spherical particles should not be less than 30%, preferably not less than 50%. The best proportion in the test is 80%.

[0090] Table 3:

[0091]

[0092]

[0093] It can be seen from Table 3 that the type of doping element Z has little effect on the cycle retention rate of the battery. The preferred chemical element is Al, and avoiding the use of W element may have a certain impact on the safety performance of the battery.

[0094] Table 4:

[0095] <![CDATA[Z a (%)]]> <![CDATA[Z b (%)]]> 1.5C / 10C cycle retention rate (%) Hot box test pass rate Example 1 1.50 2.10 89.10 8 / 8 Example 9 1.30 2.10 82.30 8 / 8 Comparative Example 5 2.20 2.10 61.30 4 / 8 Comparative Example 6 2.60 1.40 44.90 0 / 8

[0096] It can be seen from Table 4 that the content of doping element Z in region A and region B has a greater impact on the cycle retention rate of the battery. a <Z b When the battery cycle retention rate and safety test pass rate are relatively high, the cycle performance is greatly affected. a >Z b When the battery is used for a long time, the battery safety and cycle retention rate cannot be guaranteed.

[0097] Table 5:

[0098] Q 1.5C / 10C cycle retention rate (%) Hot box test pass rate Example 1 Ni 89.10 8 / 8 Embodiment 13 Co 78.30 8 / 8

[0099] It can be seen from Table 5 that the type of doped metal element Q has little effect on the cycle retention rate and safety test pass rate of the battery. In actual implementation, the selection of metal nickel or cobalt can meet the performance requirements.

[0100] In summary, on the one hand, the present application limits the order of the secondary spherical particles in the positive active material of the lithium-ion battery by region, so as to meet the demand for the high-efficiency lithium ion conduction performance of the positive active material under high-rate discharge conditions, while ensuring the structural stability of the positive active material, ensuring the cycle performance and safety performance of the battery, and extending the service life. On the other hand, the positive active material system is doped with corresponding metal and non-metal elements to improve the conductivity and structural stability of the positive active material, and support the high-rate input and output of the battery.

[0101] In the description of this specification, reference to the terms "some embodiments", "an example", or similar descriptions means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment are included in at least one embodiment or example. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0102] Although examples of the present embodiment have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present embodiment, and the scope of the present embodiment is defined by the claims and their equivalents.

Claims

1. A lithium-ion battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material coated on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material comprises at least one secondary spherical particle, the secondary spherical particle has a diameter of D and is divided into region A and region B in a three-dimensional space, wherein region A is a spherical region with a center of the secondary spherical particle as the spherical center and a diameter of m, and m=0.382D, and region B is the portion of the secondary spherical particle other than region A; the order of region A and region B satisfies: R A <R B .

2. The lithium-ion battery according to claim 1, characterized in that The order of the region A and the region B further satisfies: 1.5R A <R B .

3. The lithium-ion battery according to claim 2, characterized in that: The order of the region A and the region B further satisfies: 2R A <R B .

4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The orderliness test of the region A and the region B comprises the following steps: S21: preparing a cross-section slice of the positive electrode sheet; S22: placing the cross-section slice under a SEM and photographing it at a magnification of 1000 times to obtain a SEM image of the cross-section slice; S23: selecting one of the secondary spherical particles in the SEM image, drawing a circumscribed circle thereof, dividing the area A and the area B with the center of the circumscribed circle as the center of the secondary spherical particle, and taking the diameter of the circumscribed circle as the diameter D of the secondary spherical particle; S24: randomly select 10 complete first sub-particles in the region A, and select 30 complete second sub-particles in the region B, draw a tangent through the center of the circumscribed circle that is tangent to the first sub-particle or the second sub-particle, and the first sub-particle and the second sub-particle have a longest diameter, select the maximum angle between the tangent and the longest diameter, and record it as θ, 0°≤θ≤90°, when θ>30°, it is recorded as 0 points, when θ≤30°, it is recorded as 1 point, and the scores of all the first sub-particles and the second sub-particles are obtained in turn, and the sum of the scores of all the first sub-particles is the order degree R of the region A A The quotient of the sum of the scores of all the second sub-particles divided by 3 is the order degree R of the region B. B .

5. The lithium-ion battery according to claim 4, characterized in that: The preparation of the cross-section comprises: S11: taking one of the lithium-ion batteries, standing it at 25° C. for 4 hours, discharging it at a rate of 0.2C to its discharge cut-off voltage, and standing it for 30 minutes; S12: disassembling the lithium-ion battery and obtaining the positive electrode sheet, drying it fully, and baking it in a vacuum oven at 60° C. for 2 hours; S13: Cooling the positive electrode sheet, and preparing a cross-section of the positive electrode sheet using argon ion polishing technology.

6. The lithium-ion battery according to claim 4, characterized in that: The order R of the region A A ≤7.

7. The lithium-ion battery according to claim 4, characterized in that: The order R of the region B B ≥4.

8. The lithium-ion battery according to claim 1, characterized in that The positive electrode active material further comprises single crystal particles, and the amount of the secondary spherical particles in the positive electrode active material accounts for x≥30%.

9. The lithium-ion battery according to claim 1, characterized in that: The same element Z exists in the region A and the region B, and the element Z is one or more of Al, Zr, Sr, Sb, Mg, Ti, W, Nb, Y, Ca, Ba, B, and F.

10. The lithium ion battery according to claim 9, characterized in that: The mass percentages of the element Z in the region A and the region B are Z a and Z b , and satisfies: Z a <Z b .

11. The lithium ion battery according to claim 10, characterized in that: The Z a and Z b Further satisfaction: Z a *4R A / (2R A +R B )<Z b *R B / (R A +R B ).

12. The lithium ion battery according to claim 1, characterized in that: The metal elements with the highest content in the region A and the region B are both chemical elements Q, and the element Q is one of Ni, Co, Mn, Ti, V, Mo, and Fe.

13. An electrical device, characterized in that: Comprising a lithium ion battery according to any one of claims 1-12.

Citation Information

Cited By

  • Lithium-ion battery and electric device

    WO2026130191A1